1995
DOI: 10.1074/jbc.270.24.14255
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nuclear Translocation of Transcription Factor NF-κB by a Synthetic Peptide Containing a Cell Membrane-permeable Motif and Nuclear Localization Sequence

Abstract: To control agonist-induced nuclear translocation of transcription factor kappa B (NF-kappa B) in intact cells, cell-permeable synthetic peptides were devised. Their import into intact cells was dependent on a hydrophobic region selected from the signal peptide sequences and was verified by their inaccessibility to extracellular proteases and by confocal laser scanning microscopy. When a cell-permeable peptide carried a functional cargo representing the nuclear localization sequence of NF-kappa B p50, it inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
693
0
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 882 publications
(720 citation statements)
references
References 21 publications
20
693
0
3
Order By: Relevance
“…SN50 is a cellpermeable synthetic peptide that is known to inhibit NF-κB activation directly by blocking the translocation of the active NF-κB complex into the nucleus [41] . Our results showed that NF-κB inhibition prevented the development of chronic morphine-induced analgesic tolerance, alleviated morphine withdrawal-induced allodynia and hyperalgesia, and partially reversed the established analgesic tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…SN50 is a cellpermeable synthetic peptide that is known to inhibit NF-κB activation directly by blocking the translocation of the active NF-κB complex into the nucleus [41] . Our results showed that NF-κB inhibition prevented the development of chronic morphine-induced analgesic tolerance, alleviated morphine withdrawal-induced allodynia and hyperalgesia, and partially reversed the established analgesic tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…One approach to block this step has used cellpermeable peptides that contain the nuclear localizing sequence of p50. These peptides are thought to inhibit nuclear translocation of p50-containing dimers by saturating the nuclear import machinery responsible for the uptake of NF-kB dimers containing p50 (Lin et al, 1995;Torgerson et al, 1998;Letoha et al, 2005). However, one of the more commonly used peptides of this type, SN-50, has been reported to block nuclear translocation of a number of non-NF-kB transcription factors as well (Torgerson et al, 1998).…”
Section: Inhibitors Of Nf-kb Nuclear Translocationmentioning
confidence: 99%
“…The peptide SN50M has mutations in two of the 10 residues within the NLS of SN50 and is used as control for specificity of inhibition by SN50. 19 The effect of these inhibitors was first tested on ICAM-1 mRNA expression, which was quantitated by single-tube competitive RT-PCR as described. 2 We utilized the model system of the alveolar type II-derived A549 cells exposed to Ad.CFTR for 24 h. Figure 2a shows that Ad.CFTR up-regulated ICAM-1 mRNA levels from two-to four-fold at doses ranging from 0.1 to 50 MOI.…”
Section: Moter Adcftr Also Stimulated a 13-fold Increase In Nfkb-dementioning
confidence: 99%